Las tres arquitecturas en los contextos del medio ambiente y la sostenibilidad - Alonso García, Francisco Ramón (Observatorio Medioambiental, 2006)
Dwelling and wellbeing in today’s civilization depend on a type of construction clearly unsustainable. The concept of sustainability has been explored and defined at world fora. It affects building as well as other human activities and for the architect it is also a complex one. Architects alone cannot solve the environmental problems, but can contribute greatly to the creation of more sustainable habitats, in accordance with a set of values based on the ethics of responsibility towards environment. We are the first generation aware of transferring to our children a planet in a worse state than we got it. Then, the question is whether or not we would be able to adopt a more responsible lifestyle, whether or not we are sufficiently worried about it and if we are so, what can we change or if our market economy if out of control. Can the answer be found in education?
Keywords: Architecture; Education; Environment; Bioclimatic; Sustainable; Urban